2D and 3D Ag(I) coordination polymers with a 2-methylimidazole substituted cyclotriphosphazene ligand: Structures and dye adsorption properties - Duyar, Ceyda; Pendar, Afranur; Bektas, Nihal; Zorlu, Yunus; Davarci, Derya (Pergamon-Elsevier Science Ltd, 2023)
Coordination polymers are a promising crystalline framework for dye capture and separation in recent years. We are reporting herein the two new, Ag(I) coordination polymers, namely {[Ag3(MeIm-Cp)2](NO3)3}n (1) and {[Ag (MeIm-Cp)](CH3PhSO3)} (2), were synthesized from hexapodal-shaped 2-methylimidazole substituted cyclotriphosphazene, (MeIm-Cp). MeIm-Cp was characterised by 1H NMR, 31P NMR and mass analysis. Structure of each isolated compounds were assigned by single crystal X-ray crystallography. In complex 1, MeIm-Cp has a & kappa;6N coordination mode by connecting six Ag(I) ions to constitute a 3D coordination framework whereas the ligand in complex 2 displays & kappa;4N coordination mode via linking four Ag(I) ions together to create a 2D coordination polymer. Topologically, coordination polymer 1 exhibits a 4,4,6-connected three nodal net with point symbol {44.62}3{46.68.8}2, while coordination polymer 2 displays a four-connected network having the point symbol {43.63}. According to thermogravimetric analysis, the thermal stability of MeIm-Cp is higher than complexes. The synthesized coordination polymers were used for the adsorption of some cationic and anionic organic dyes in aqueous media, Dye adsorption studies were performed out using UV-Vis. absorption spectroscopy. Adsorption experiments show that complex 1 removes the anionic methyl orange (MO) and tartrazine (E102) from water but shows no adsorption behaviour toward the cationic methylene blue (MB).
Keywords: Ag(I) coordination polymers; Cyclotriphosphazene; 2-Methylimidazole; Dye adsorption